Hidden treasures: Human-made aquatic ecosystems harbour unexplored opportunities - Koschorreck, Matthias; Downing, Andrea S; Hejzlar, Josef; Marcé, Rafael; Laas, Alo; Arndt, Witold G; Keller, Philipp S; Smolders, Alfons J P; van Dijk, Gijs; Kosten, Sarian (Ambio, 2020)
Artificial water bodies like ditches, fish ponds, weirs, reservoirs, fish ladders, and irrigation channels are usually constructed and managed to optimize their intended purposes. However, human-made aquatic systems also have unintended consequences on ecosystem services and biogeochemical cycles. Knowledge about their functioning and possible additional ecosystem services is poor, especially compared to natural ecosystems. A GIS analysis indicates that currently only ~ 10% of European surface waters are covered by the European Water Framework directive, and that a considerable fraction of the excluded systems are likely human-made aquatic systems. There is a clear mismatch between the high possible significance of human-made water bodies and their low representation in scientific research and policy. We propose a research agenda to build an inventory of human-made aquatic ecosystems, support and advance research to further our understanding of the role of these systems in local and global biogeochemical cycles as well as to identify other benefits for society. We stress the need for studies that aim to optimize management of human-made aquatic systems considering all their functions and to support programs designed to overcome barriers of the adoption of optimized management strategies.
Keywords: Fishes; Animals; Humans; lidé; zvířata; ryby; ekosystém; Ecosystem